Wykorzystanie modeli ryzyka konkurencyjnego w celu szacowania czasu trwania aktywności zawodowej - Landmesser, Joanna Małgorzata (Application of Competing Risk Models to Estimation of Employment Duration, 2007)
The aim of this paper is to model the duration of employment period in Poland using the survival analysis. Estimating the noncompeting risk model and competing risk model we calculate the conditional probabilities of transition from employment state to the unemployment state (exits to unemployment and job search or exits to out of the labour force, e.g. retirement, disability). We estimate hazard rate models to assess the effect of gender, age, education level and place of residence on the individual's employment duration. For the estimation, we use data from the Labour Force Survey in Poland (Badanie Aktywności Ekonomicznej Ludności Polski BAEL).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 542-550